Hepatic and renal trace element concentrations in American alligators (Alligator mississippiensis) following chronic dietary exposure to coal fly ash contaminated prey. (July 2016) - Tuberville, Tracey D.; Scott, David E.; Metts, Brian S.; Finger, John W.; Hamilton, Matthew T.
Abstract: Little is known about the propensity of crocodilians to bioaccumulate trace elements as a result of chronic dietary exposure. We exposed 36 juvenile alligators ( Alligator mississippiensis ) to one of four dietary treatments that varied in the relative frequency of meals containing prey from coal combustion waste (CCW)-contaminated habitats vs. prey from uncontaminated sites, and evaluated tissue residues and growth rates after 12 mo and 25 mo of exposure. Hepatic and renal concentrations of arsenic (As), cadmium (Cd) and selenium (Se) varied significantly among dietary treatment groups in a dose-dependent manner and were higher in kidneys than in livers. Exposure period did not affect Se or As levels but Cd levels were significantly higher after 25 mo than 12 mo of exposure. Kidney As and Se levels were negatively correlated with body size but neither growth rates nor body condition varied significantly among dietary treatment groups. Our study is among the first to experimentally examine bioaccumulation of trace element contaminants in crocodilians as a result of chronic dietary exposure. A combination of field surveys and laboratory experiments will be required to understand the effects of different exposure scenarios on tissue residues, and ultimately link these concentrations with effects on individual health. Graphical abstract: Highlights: Alligators chronically exposed to contaminated prey bioaccumulate trace elements. Kidney and liver concentrations of arsenic, selenium and cadmium varied with dose. Only selenium concentrations approached toxicological benchmarks. Neither growth nor body condition were affected by dose. Abstract : Chronic dietary exposure can result in significant bioaccumulation of trace elements in juvenile alligators.